The origins of fair play - Ken Binmore (Max Planck Institute of Economics, 2006)
This paper gives a brief overview of an evolutionary theory of fairness. The ideas are fleshed out in Binmore's book 'Natural Justice' (Oxford University Press, New York, 2005.), which is itself a condensed version of his earlier two-volume book 'Game Theory and the Social Contract' (MIT Press, Cambridge, MA, 1994 and 1998).
Keywords: 330